Islamic Sciences and Their Impact on Promoting Moral Values and Developing Social and Educational Awareness - Hassan, Prof. Dr. Ahmed Manaf Hassan (Sulaimani Journal for Humanities, 2026)
This study explores the profound role of Islamic sciences in shaping both individual and societal development through the promotion of ethical values and the enhancement of social and educational awareness. The research addresses a central question: how can Islamic sciences be effectively utilized to confront contemporary moral and societal challenges؟ Using an inductive and analytical methodology, the research examines foundational Islamic texts and analyzes their relevance to modern social and educational contexts, supported by insights from contemporary academic literature. The paper outlines the foundational concepts and objectives of Islamic sciences, emphasizing their significance in reinforcing sound belief, organizing social life, and fostering virtues such as justice, honesty, compassion, and tolerance. It also demonstrates the sciences’ role in cultivating civic responsibility and a strong sense of national identity. Furthermore, the study proposes practical mechanisms to activate Islamic sciences in modern life—through curriculum development, the strategic use of modern media and digital platforms, and strengthening academic research addressing current social and educational issues. The study concludes that Islamic sciences represent a comprehensive and dynamic knowledge system capable of producing ethically-grounded and socially aware communities—provided they are approached through an integrated methodology that balances tradition with modernity.
Keywords: Islamic sciences; ethical values; social awareness; education; curricula; digital media; moderate Islamic thought